Faktor- faktor yang mempengaruhi kebijakan hutang pada perusahaan non-keuangan yang terdaftar di bursa efek Indonesia - ITA TRISNAWATI (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this study was to get empirical evidence influence the insider ownership, institutional ownership, dividend policy, firm growth, profitability, free cash flow, firm size, asset structure to corporate debt policy. This research focus on non-financial companies listed in Indonesia Stock Exchange for the period of 2009 until 2011. The data collection used purposive sampling method by using 53 companies meet the criteria and take as sample. The statistical method used in this research is multiple regressions to see the contribution of each variable influence debt policy. The results of this study shows that insider ownership, dividend policy, free cash flow, and firm size variable does not have influence towards debt policy. In the other hand, institutional ownership, firm growth, profitability, and asset structure have influence toward debt policy